Diabetes-related distress, depression and distress-depression among adults with type 2 diabetes mellitus in Malaysia - Chew, Boon How; Vos, Rimke; Mohd Sidik, Sherina; Rutten, Guy E. H. M. (Public Library of Science, 2016)
Type 2 diabetes mellitus (T2DM) brings about an increasing psychosocial problem in adult patients. Prevalence data on and associated factors of diabetes related distress (DRD) and depression have been lacking in Asia. This study aimed to examine the prevalence of DRD and depression, and their associated factors in Asian adult T2DM patients. This study was conducted in three public health clinics measuring DRD (Diabetes Distress Scale, DDS), and depression (Patient Health Questionnaire, PHQ). Patients who were at least 30 years of age, had T2DM for more than one year, with regular follow-up and recent laboratory results (< 3 months) were consecutively recruited. Associations between DRD, depression and the combination DRD-depression with demographic and clinical characteristics were analysed using generalized linear models. From 752 invited people, 700 participated (mean age 56.9 years, 52.8% female, 52.9% Malay, 79.1% married). Prevalence of DRD and depression were 49.2% and 41.7%, respectively. Distress and depression were correlated, spearman’s r = 0.50. Patients with higher DRD were younger (OR 0.995, 95% CI 0.996 to 0.991), Chinese (OR 1.2, 95% CI 1.04 to 1.29), attending Dengkil health clinic (OR 1.1, 95% CI 1.00 to 1.22) and had higher scores on the PHQ (OR 1.1, 95% CI 1.04 to 1.06). Depression was less likely in the unmarried compared to divorced/separately living and those attending Dengkil health clinic, but more likely in patients with microvascular complications (OR 1.4, 95% CI 1.06 to 1.73) and higher DDS (OR 1.03, 95% CI 1.02 to 1.03). For the combination of DRD and depression, unemployment (OR 4.7, 95% CI 1.02 to 21.20) had positive association, whereas those under medical care at the Salak health clinics (OR 0.28, 95% CI 0.12 to 0.63), and those with a blood pressure > 130/80 mmHg (OR 0.53, 95% CI 0.32 to 0.89) were less likely to experience both DRD and depression. DRD and depression were common and correlated in Asian adults with T2DM at primary care level. Socio-demographic more than clinical characteristics were related to DRD and depression.